Role of granulocyte-macrophage colony stimulating factor (GM-CSF) in the pathogenesis of adult pulmonary histiocytosis X. Issue 6 (June 1996) - Tazi, A; Bonay, M; Bergeron, A; Grandsaigne, M; Hance, A J; Soler, P
Abstract : BACKGROUND: Pulmonary histiocytosis X is a disorder characterised by the presence of destructive granulomas preferentially involving distal bronchioles, that contain numerous activated Langerhans' cells. Recent studies have shown that granulocyte-macrophage colony stimulating factor (GM-CSF), which is produced by normal bronchiolar epithelium, may play an important part in the distribution and differentiation of Langerhans' cells. The aim of this study was to evaluate the role of this factor in the pathogenesis of pulmonary histiocytosis X. METHODS: Four patients with pulmonary histiocytosis X were examined by immunohistochemical techniques for GM-CSF and CD1a surface molecules. RESULTS: In early lesions the epithelium of bronchioles affected by the disease was strongly positive for GM-CSF and infiltrated by numerous CD1a+ Langerhans' cells organised into granulomas. In contrast, the expression of GM-CSF was substantially lower in bronchioles not affected by the disease, and these bronchioles contained few Langerhans' cells. When destruction by histiocytosis X lesions was more advanced, only remnants of bronchiolar epithelium could occasionally be identified; these remained strongly reactive for GM-CSF. Langerhans' cells within granulomas also moderately expressed this cytokine. CONCLUSIONS: These results support the hypothesis that GM-CSF could be one of the factors responsible for the local accumulation of lymphostimulatory Langerhans' cells in early lesions of pulmonary histiocytosis X.